A Role for Resistin in the Ovary During the Estrous Cycle - Rak-Mardyła, A.; Duda, M.; Gregoraszczuk, E. Ł. (Hormone and Metabolic Research, 2014)
In a previous study, we showed that resistin expression increased during ovarian follicle development in prepubertal pigs and had direct effects on steroidogenesis, suggesting an important role for resistin in the ovary during puberty. To determine its potential regulatory role in the ovary during the estrous cycle, using real-time PCR, immunoblotting, immunohistochemistry, and ELISA methods, we quantified the expression, immunolocalization and concentration of resistin in different sized ovarian follicles (small, 2–4 mm; medium, 4–6 mm; and large, 8–12 mm) in mature pigs. We then determined the effects of recombinant resistin (0.1, 1, and 10 ng/ml) on steroid hormone (progesterone-P4, androstendione-A4, testosterone-T, and estradiol-E2) secretion and steroidogenic enzyme (3βHSD, CYP17A1, 17βHSD, and CYP19A1) gene and protein expression in ovarian follicles. We found no differences in the resistin expression between all of the examined follicles. Immunostaining analysis also showed resistin expression in the cytoplasm of both granulosa and theca cells, where it was localized more abundantly in the granulosa cells compared to the theca cells. Recombinant resistin direct stimulated P4, A4, and T secretion via increased expression of 3βHSD, CYP17A1, and 17βHSD, suggesting an autocrine and/or paracrine regulatory role in the porcine ovary during the estrous cycle.
Keywords: resistin; porcine ovarian follicle; estrous cycle; steroidogenesis